The role of Multilingualism in Finding Employment in the Iraqi Kurdistan Region - Tara Mushir Salih (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Multilingualism means that someone speaks more than two or three languages other than their mother tongue. The Kurdistan Region needs a language management policy and plan. As a multicultural and multilingual region, English and Arabic are also used in most schools, universities, colleges, and institutes, except for some schools for religious and ethnic minorities such as Assyrian and Turkmen Turkmen are used for education, which requires good governance to protect the rights of all religions and ethnic groups in Kurdistan while protecting the Kurdish language, which is one of the most important factors of national identity That the Kurdish people can benefit from it and keep up with the procession of globalization, progress, science and technology. This research is entitled (The Role of Multilingualism in Job Search in the Iraqi Kurdistan Region). The research consists of two parts: introduction, content, results, and sources. In addition, the abstract is written in both Arabic and English. The first part is entitled (Multilingualism and its benefits), which includes the following topics: the concept and definition of multilingualism, the reasons for multilingualism, the benefits of multilingualism in the Kurdistan Region. The second part is entitled (The Role of Multilingualism in Finding Jobs), which includes the following topics: multilingualism in the Kurdistan Region, and field research.